On One of the Weapon Types of Cimmerian Time - Klochko, D.D. (Археологія, 2020)
The article is dedicated to the analysis of bimetallic swords and daggers of Cimmerian time, which were found both at Ukrainian territory and neighboring countries. The previously known and new findings are analyzed.